Anticipated nursing care as perceived by nursing students: Findings from a qualitative study - Lisa Lunardelli; Matteo Danielis; Michela Bottega; Alvisa Palese (Nursing Open, 2021)
Abstract Aim To explore the perceptions of nursing students on the phenomenon of anticipated nursing care. Design A descriptive‐qualitative study was performed in 2019 according to the Consolidated Criteria for Reporting Qualitative Research principles. Methods Data were collected using 16 face‐to‐face, audio‐recorded interviews across four Italian Bachelor of Nursing degrees. Then, content analysis was performed, identifying, analysing and describing the anticipated nursing care phenomenon as perceived by nursing students. Results Administering medications, providing fundamentals of care, managing some clinical procedures, freeing up the patient's bed and starting the shifts early emerged as the most anticipated nursing interventions. Stable, older patients who were more functionally dependent were reported to receive some fundamental nursing care before the expected time, while older, stable and more independent patients were used to receiving medications in advance. Anticipated nursing care is triggered by factors at the time management, resource, programming, professional and organizational levels.